2020
DOI: 10.1080/14036096.2019.1697356
|View full text |Cite
|
Sign up to set email alerts
|

Ethically-speaking, what is the most reasonable way of evaluating housing outcomes?

Abstract: This paper addresses one of the most fundamental, but least considered, questions in housing research: how should we ultimately evaluate housing outcomes? Rejecting the fact vs value dichotomy so dominant in the social sciences, this paper draws on the work of Amartya Sen and Hilary Putnam to critically assess the ethical assumptions behind three commonly adopted "informational spaces" for evaluating housing outcomes: economic, subjective and "objective" metrics. It argues that all three fail to account for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The capabilities approach is increasingly recognized as a valuable lens through which to explore and illuminate the value of home, and the negative impacts of various forms of housing deprivation on people's lives (Kimhur 2020;Foye 2020). It is a theoretical paradigm that focuses on what people are able to do and be -the real opportunities available to them -as the appropriate way of thinking about social justice (Sen 1992;Nussbaum 2011).…”
Section: Capability Theory and Control Over One's Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The capabilities approach is increasingly recognized as a valuable lens through which to explore and illuminate the value of home, and the negative impacts of various forms of housing deprivation on people's lives (Kimhur 2020;Foye 2020). It is a theoretical paradigm that focuses on what people are able to do and be -the real opportunities available to them -as the appropriate way of thinking about social justice (Sen 1992;Nussbaum 2011).…”
Section: Capability Theory and Control Over One's Environmentmentioning
confidence: 99%
“…We do so using tools provided by the capabilities approach, arguing that while control over one's environment has been recognized as important by capabilities theorists (most notably, Nussbaum 2011), control over one's immediate living environment remains underappreciated as a core facet of such control, something that may reflect the dominant methodologies deployed to construct "central capabilities" lists. In taking the capabilities approach as the primary jumping off point, 1 we contribute to the nascent tradition of normative housing scholarship that grapples explicitly with questions of what housing and home should be like given our understandings of human flourishing (Taylor 2018;Foye 2020;Kimhur 2020). In doing so, we seek to both complement -and go beyond -the extensive work of social theorists documenting the complex (and sometimes contradictory) "meanings of home" from a non-normative perspective (Easthope 2004;Mallett 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Critically, these studies have established the centrality of housing to a 'well-lived' life and as suggested by Batterham (2020), this matter should now be beyond question. There is also growing consensus that capabilities are a highly valuable informational base for the evaluation of housing outcomes, providing researchers with a framework which extends the traditional boundaries of research and more effectively captures the plurality of ends which users value (Clapham et al, 2018;Foye, 2021;Kimhur, 2020;Watts & Fitzpatrick, 2020). It is important to note, nonetheless, that despite its ethical merits, few studies have evaluated housing outcomes using 'capabilities' (rather than functionings), as these are largely abstract hypothetical states and thus difficult to measure (Foye, 2020).…”
Section: Housing and Capabilitiesmentioning
confidence: 99%
“…Since then, however, there has been little research on how Sen's idea can be applied to housing discussion. In recent years, housing research using the capability approach has increased, but there are still few studies that rigorously examine the implications of the capability approach for housing policies and their applications, with only some recent exceptions (Foye 2021;Taylor 2019). In multiple housing studies, the capability approach has been used as a framework to analyse particular issues, such as homelessness, slums, and older tenants (Batterham 2018;Evangelista 2010;Frediani 2007;Haffner and Elsinga 2019;Morris 2012;Nicholls 2010), or as a philosophical foundation to advocate housing as a fundamental element of human rights, human flourishing and freedom (Fitzpatrick, Bengtsson, and Watts 2014;King 2003).…”
Section: Potential Ideas From the Capability Approachmentioning
confidence: 99%